Systemic cytokine response following exercise-induced muscle damage in humans - Philippou, A.a , Bogdanis, G.b , Maridaki, M.b , Halapas, A.a , Sourla, A.c , Koutsilieris, M.a (Clinical Chemistry and Laboratory Medicine, 2009)
Background: Muscle adaptation which occurs following eccentric exercise-induced muscle damage has been associated with an acute inflammatory response. The purpose of this study was to investigate serum interleukin-6 (IL-6), osteoprotegerin and receptor activator of nuclear factor kB ligand (OPG/RANKL) concentrations following muscle damage. We measured changes for several days following muscle damage. Methods: Ten healthy young males performed an eccentric exercise protocol using their quadriceps. Blood samples were withdrawn before and at 6 h, 2 days, 5 days and 16 days post-exercise. Functional and clinical measurements were performed before, and on days 1, 2, 5, 8, 12 and 16 post-exercise. Results: The exercise protocol resulted in muscle damage, indicated by changes in biochemical markers. An increase in IL-6 and OPG, and a decrease in RANKL concentrations were seen at 6 h and on day 2 post-exercise; the OPG:RANKL ratio was increased at 6 h post-exercise (p<0.05). Conclusions: Changes in IL-6 and OPG/RANKL system may represent systemic responses in muscle inflammation and repair processes. However, further studies are needed to elucidate a potential systemic and/or local role of the OPG/RANKL system in skeletal muscle repair. © 2009 by Walter de Gruyter.